Positivité et négativité du goût culturel - Hervé Glevarec; Michel Pinet (Communication)
The authors analyze data on taste and inappetence regarding cinematographic genres taken from the 2008 national survey of cultural practices in France, in order to describe these sociocultural universes and the different ways appetence and inappetence, with respect to cinematographic genres, can combine. The authors argue that variables other than socioprofessional determination now structure cinematographic preferences, and show that negation of taste (taste as aversion) is but one expression of the principle of appetence operating across different cultural genres.